Macrocognition in teams : theories and methodologies - Letsky, Michael P. (Human factors in defence., 2008)
Macrocognition in Teams provides readers with a greater understanding of the macrocognitive processes which support collaborative team activity, showcasing current research, theories, methodologies and tools. It will be of direct relevance to academics, researchers and practitioners interested in group/team interaction, performance, development and training.